CONCEPT SINCERE IN NOVEL HAFALAN SHALAT DELISA MASTERPIECE TERE LIYE - Leny marlina marlina; Elmustian '; Abdul Jalil Jalil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: Concept Sincere  in Novel Hafalan Shalat Delisa Masterpiece Tere Liye. The purpose of this study was to describe the Concept Sincere  in Novel Hafalan Shalat Delisa Masterpiece Tere Liye. The method used in this research is descriptive method. Concept Sincere  in Novel Hafalan Shalat Delisa Masterpiece Tere Liye, based on the results of the analysis consists of eight elements. The sincere concept include: (a) husnuzhan is prejudiced either, (b) istiqamah is firm stance and always consistent, (c) trust surrender to the will of Allah, (d) the patient is self-restraint or control, (e), namely thanks gratitude, (f) the attitude of the ascetic who is not crazy about world affairs and glitter, (g) forgiving is forgiving, and (h) wara 'is docile and obedient to God. Keywords: Concept of sincere, Literature and Novels